PELATIHAN PENYUSUNAN MODUL AJAR UNTUK EFEKTIVITAS KURIKULUM MERDEKA BAGI GURU SENI - Dwi Kusumawardani; Didin Supriadi; M. Asril; Maulita Meysanti Setiawan; Syiva Restu Shabrina (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
This training activity is a service program for Fine Arts/Music/Dance subject teachers at DKI Jakarta MGMP group high schools.  The training aims to increase teachers' understanding regarding the implementation of the Merdeka Curriculum into teaching modules. The priority for solving problems through this training is misconceptions about writing the substance of teaching modules, due to teachers' lack of understanding of the implementation of Merdeka Curriculum concepts into teaching modules, and teachers' lack of understanding in writing substance in teaching modules. So, training activities are designed to overcome these two problems.  The training method implements retraining. Training equivalent to 22 JP, the activities are (1) refreshing material on the relationship between the Merdeka Curriculum and teaching modules as well as teaching module writing simulations carried out in 5 JP; (2) independent practice in creating teaching modules with the given format, and mentoring in 14 JP; (3) reviewing the results of writing teaching module with a focus on the substance of 3 JP.  The results of the analysis of teaching modules written by training participants show that misconceptions in writing the substance of teaching modules can be minimized and understanding increased. Participants who actively participate in training can write substance teaching modules correctly.                                               Keywords: training; preparation of teaching modules; retraining method   Abstrak  Kegiatan pelatihan ini merupakan program pengabdian untuk para guru pengampu mata pelajaran Seni Rupa/Musik/Tari di SMA dalam kelompok MGMP DKI Jakarta.  Pelatihan bertujuan untuk meningkatkan pemahaman guru mengenai implikasi Kurikulum Merdeka ke dalam modul ajar.  Masalah prioritas yang ditangani melalui pelatihan ini adalah miskonsepsi dalam penulisan subtansi modul ajar, karena kurangnya pemahaman guru terhadap implikasi konsep Kurikulum Merdeka ke dalam modul ajar, dan kurangnya pemahaman guru dalam menulis subtansi pokok bahasan  modul ajar.  Oleh karena itu, kegiatan pelatihan dirancang untuk mengatasi kedua masalah tersebut.  Metode pelatihan menerapkan retraining. Pelatihan setara 22 JP, kegiatannya: (1) penyegaran materi tentang kaitan Kurikulum Merdeka dengan modul ajar dan simulasi penulisan modul ajar dilaksanakan 5 JP; (2) latihan mandiri membuat modul ajar dengan format yang telah disediakan dan pendampinan dilaksanakan 14 JP; dan (3) review hasil penulisan modul ajar terfokus kepada subtansi selama 3 JP.  Hasil analisis terhadap modul ajar yang telah ditulis oleh peserta pelatihan menunjukkan bahwa miskonsepsi dalam penulisan subtansi modul ajar dapat diminimalisir dan terjadi peningkatan pemahaman. Peserta yang aktif dalam pelatihan dapat menulis subtansi modul ajar dengan benar.   Kata Kunci: pelatihan; penyusunan modul ajar; metode retraning